Pembangunan Hukum Berdasarkan Cita Hukum Pancasila - Tami Rusli (PRANATA HUKUM, 2011)
The development of the national law based Pancasila as "rechtsidee ", at the present time so many aspects of community has changed and developed rapidly. This change, of course, greatly influenced the development of existing Indonesia law. Development in all areas was always carried out, including the development of law through legal reform in order to develop a national law based on Pancasila. The Indonesian revolution that culmination point as Proclamation of Independence of the Republic of Indonesia creating a national law, he relief only in political terms only. Should be to building a legal system on the basis of new spiritual values of Pancasila. Ideas such as these provide a broad place to explore the principles of customary law in and regulations to conform with the ideals of Indonesian law based Pancasila and Indonesia Constitution year 1945